COVID-19 fatality rates in hospitalized patients: A new systematic review and meta-analysis - Alexandre Baptista; Ana M. Vieira; Eunice Capela; Pedro Julião; Ana Macedo (Elsevier, 2023)
Background: SARS-COV2 or COVID-19 disease is an infectious illness that emerged for the first time at the end of 2019, in Wuhan, China and rapidly turned out to be an international pandemic with deleterious effects all over the world. In March 2021, A. Macedo et al., has published the first meta-analysis of hospital mortality, so the authors decided to update those data at a time of emergence of new therapies and increasing vaccination rates. Methods: As the outcome of interest was the mortality in hospitalized general patients, the authors looked for articles evaluating the clinical characteristics of those patients, consulting PUBMED (The US National Library of Medicine) and EMBASE (Medical database) in an independent selection using predefined terms of search. A meta-analysis random-effect model was estimated using Mantel-Haenszel method. Heterogeneity among studies was tested using Tau2 statistics and Chi2 statistics. Results: In a first instance 25 articles were included for final analysis with a total of 103,840 patients, but as the goal was to update the anterior data, these studies were analysed together with the 21 studies of the previous meta-analysis, with a total of 114609 patients. The mortality rate of COVID-19 general patients admitted to the hospital was 16% (95% CI 12; 21, I2 =100%). Conclusion: Global hospital mortality of COVID-19 of general patients was 16%, with quite different rates according to the different geographic areas analysed.